Depois do projeto-piloto: análise compreensiva da implementação dos novos playgroups for inclusion "Grupos aprender, brincar, crescer" - Castro, Catarina Alexandra da Cruz de (2019)
Playgroups are a non-formal educational response for children under pre-school age and their caregivers to attend together, play and socialize. The playgroup model has been present in several countries, recently taking its first steps in Portugal with the pilot-project Playgroups for Inclusion (or “Grupos Aprender, Brincar, Crescer”, GABC). After its encouraging results, the goal has been to disseminate this service. This dissertation aimed at a comprehensive analysis of these new playgroups, focusing on its quality, similarly to the monitoring process carried out during the pilot. Two GABCs were invited to take part in this comprehensive analysis. Interviews with playgroup facilitators (N=4) and with participating caregivers (N=10) provided an insight on their expectations, experiences and perceptions of playgroup implementation and participation. Complementarily, GABC sessions were videotaped in order to assess its process quality with an observational tool – the Playgroups Environment Rating Scale (PERS; Alexandre et al., 2016), developed by the pilot-project monitoring team for the purpose of evaluating quality in a non-formal educational setting with such particular characteristics as the playgroups.